Continuous Local Anesthetic Infusion via Chest Wall Catheter for Analgesia After Thoracic Surgery in Neonates: A Case Series. Issue 10 (October 2021) - Dixit, Divya; Choudhry, Dinesh K.; Reichard, Kirk
Abstract : Pain management options in neonates after thoracotomy have traditionally been limited to intravenous opioids and caudal catheters. However, because of increasing familiarity with ultrasound imaging, erector spinae and paravertebral nerve blocks are being performed more frequently. For thoracic procedures, we describe a case series of 4 neonates involving ropivacaine infusion via an extrathoracic chest wall catheter placed by the surgeon. This technique requires less time, is less invasive, does not require ultrasound, and enabled us to accomplish tracheal extubation in the operating room immediately after surgery, and decreased postoperative opioid use in the neonatal intensive care unit.